Meta‐analysis of ecosystem services associated with oyster restoration. Issue 1 (8th September 2022) - Smith, Rachel S.; Cheng, Selina L.; Castorani, Max C. N.
Abstract: Restoration of foundation species promises to reverse environmental degradation and return lost ecosystem services, but a lack of standardized evaluation across projects limits understanding of recovery, especially in marine systems. Oyster reefs are restored to reverse massive global declines and reclaim valuable ecosystem services, but the success of these projects has not been systematically and comprehensively quantified. We synthesized data on ecosystem services associated with oyster restoration from 245 pairs of restored and degraded reefs and 136 pairs of restored and reference reefs across 3500 km of U.S. Gulf of Mexico and Atlantic coastlines. On average, restoration was associated with a 21‐fold increase in oyster production (mean log response ratio = 3.08 [95% confidence interval: 2.58–3.58]), 34–97% enhancement of habitat provisioning (mean community abundance = 0.51 [0.41–0.61], mean richness = 0.29 [0.19–0.39], and mean biomass = 0.69 [0.39–0.99]), 54% more nitrogen removal (mean = 0.43 [0.13–0.73]), and 89–95% greater sediment nutrients (mean = 0.67 [0.27–1.07]) and organic matter (mean = 0.64 [0.44–0.84]) relative to degraded habitats. Moreover, restored reefs matched reference reefs for these ecosystem services. Our results support the continued and expanded use of oyster restoration to enhance ecosystem services of degraded coastal systems and match many functions provided by reference reefs. Abstract : Article Impact Statement :Restored oyster reefs enhance ecosystem services relative to degraded habitats and match those of references, supporting future restoration. Resumen: La restauración de especies fundadoras promete revertir la degradación ambiental y restituir servicios ambientales perdidos, pero la falta de evaluación estandarizada de proyectos limita la comprensión de la recuperación, especialmente en sistemas marinos. Los bancos de ostión son restaurados para revertir declinaciones globales masivas y recuperar servicios ecosistémicos valiosos, pero el éxito de estos proyectos no ha sido cuantificado sistemática ni integralmente. Sintetizamos datos sobre los servicios ecosistémicos asociados con la restauración de ostiones de 245 pares de bancos restaurados y degradados y 136 pares de bancos restaurados y de referencia a lo largo de 3500 km de costa del Golfo de México y Atlántico norteamericanos. En promedio, la restauración se asoció con un incremento de 21 veces en la producción de ostión (media de proporción de respuesta log = 3.08 [95% IC 2.58‐3.58]), mejoras entre 34 y 97% en el aprovisionamiento de hábitat (abundancia media = 0.51 [0.41‐0.61], riqueza media = 0.29 [0.19‐0.39], y biomasa media = 0.69 [0.39‐0.99]), 54% más remoción de nitrógeno (media = 0.43 [0.13‐0.73]), y 89–95% más nutrientes en sedimento (media = 0.67 [0.27‐1.07]) y materia orgánica (media = 0.64 [0.44‐0.84]) en relación con hábitats degradados. Más aun, estos servicios ecosistémicos de los bancos restaurados fueron muy similares en los bancos de referencia. Nuestros resultados sustentan el uso continuo y expandido de la restauración de ostiones para mejorar los servicios ecosistémicos de sistemas costeros degradados y que sean parecidos a las numerosas funciones proporcionadas por los bancos de referencia.